The Effect of the Board of Directors and Environmental Performance on Financial Performance - Sari, Wulan Ratna; Wahyuantika, Deanisa; Pratama, Bima Cinintya; Wardani, Anggun Tri; Marhamah, Umu (Proceedings Series on Social Sciences & Humanities, 2022)
This study aimed to determines the impact of board and environmental performances on financial performances. The population of this survey is the Islamic bank for the period 2016-2021. The sampling method used is purposive sampling, so the sample are 73 companies that meet the criteria. The data analysis method used is multiple regression analysis using SPSS programs. The results of this survey show that the age diversity of the board has a positive impact on financial performance, but it is not important. Board education does not affect financial performance. Environmental performance does not affect financial performance.